Dynamic buffer tuning: an ambience-intelligent way for digital ecosystem success - Wong, Jackei; Wong, Allan; Lin, Wilfred; Dillon, Tharam S. (Institute of Electrical and Electronics Engineers (IEEE), 2008)
Ambient intelligence is an important element for the success of digital ecosystems which usually are made up of many collaborating distributed nodes. The operations of these nodes affect one another as chain reactions. When one node had failed, it could bring down the whole ecosystem. Dynamic buffer tuning is an ambience-intelligent mechanism because it has the ability to sense the ambient changes and then makes necessary proactive changes on the fly to avoid buffer overflow. As a result the end-to-end communication channel is more dependable, leading to shorter response time and happier clients. Therefore, dynamic buffer tuning should be generally beneficial to digital ecosystem system performance. In this paper we demonstrate this point by using the FLC (Fuzzy Logic Controller) dynamic buffer tuner to quicken the pervasive medical consultation response of the TCM (Traditional Chinese Medicine) Pervasive Digital HealthCare System as an example.